Analysis of Snail1 function and regulation by Twist1 in palatal fusion - Yu, Wenli; Zhang, Yanping; Ruest, L. Bruno; Svoboda, Kathy K. (Frontiers in Physiology, 2013)
Palatal fusion is a tightly controlled process which comprises multiple cellular events, including cell movement and differentiation. Midline epithelial seam (MES) degradation is essential to palatal fusion. In this study, we analyzed the function of Snail1 during the degradation of the MES. We also analyzed the mechanism regulating the expression of the Snail1 gene in palatal shelves. Palatal explants treated with Snail 1 siRNA did not degrade the MES and E-cadherin was not repressed leading to failure of palatal fusion. Transforming growth factor beta 3 (Tgf3) regulated Snail1 mRNA, as Snail1 expression decreased in response to Tgf3 neutralizing antibody and a PI3K inhibitor. Twist1, in collaboration with E2A factors, regulated the expression of Snail1. Twist1/E47 dimers bond the Snail1 promoter to activate expression. Without E47, Twist1 repressed Snail1 expression. These results support the hypothesis that Tgfβ3 may signal through Twist1 and then Snail1 to downregulate E-cadherin expression during palatal fusion.